The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1471-2091-15-18
|View full text |Cite
|
Sign up to set email alerts
|

Galloyl-RGD as a new cosmetic ingredient

Abstract: BackgroundThe cosmetics market has rapidly increased over the last years. For example, in 2011 it reached 242.8 billion US dollars, which was a 3.9% increase compared to 2010. There have been many recent trials aimed at finding the functional ingredients for new cosmetics. Gallic acid is a phytochemical derived from various herbs, and has anti-fungal, anti-viral, and antioxidant properties. Although phytochemicals are useful as cosmetic ingredients, they have a number of drawbacks, such as thermal stability, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, gallic acid is thermally unstable, which makes its use as cosmetic ingredient difficult. In our previous study, we confirmed that galloyl-RGD has higher thermal stability than gallic acid (21). In this study, we found galloyl-RGD inhibits melanogenesis through a similar mechanism with that of gallic acid (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, gallic acid is thermally unstable, which makes its use as cosmetic ingredient difficult. In our previous study, we confirmed that galloyl-RGD has higher thermal stability than gallic acid (21). In this study, we found galloyl-RGD inhibits melanogenesis through a similar mechanism with that of gallic acid (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study, in order to overcome these limitations, we synthesized galloyl-RGD ( Fig. 1a) by combining gallic acid with arginine, glycine and asparaginic acid (RGD peptide) by solid-phase peptide synthesis (21). We found that galloyl-RGD is stable at a wider range of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical analysis performed on ex vivo skin explants confirmed that GEKG induced the production of pro-collagen, hyaluronic acid, and fibronectin. The galloyl-RGD, which is a tripeptide conjugated to gallic acid, was differently characterized for its capacity to inhibit free radical formation in HaCaT keratinocytes at the concentration of 50 ppm, and to suppress L-3,4-DihydrOxyPhenylAlanine (L-DOPA) formation and oxidation when used at higher doses (Dae et al, 2014). A Palmitoyl tetrapeptide, which represented a fragment of an immunoglobulin G, was proven to decrease IL-6 secretion in a basal setting, and served as an anti-inflammatory compound after exposure to UVB-irradiation.…”
Section: Bioactive Peptides In the Cosmetic Industrymentioning
confidence: 99%
“… 9 Though GA is used in the cosmetics and food industries because of these beneficial effects, its formulation tends to be unstable. 10 We thus developed (galloyl) 2 –KTPPTTP (Gal 2 –Pep) in order to increase the stability of GA by binding it to the PGC-1α-derived peptide TTPTTP.…”
Section: Introductionmentioning
confidence: 99%